1992
DOI: 10.1139/m92-093
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Bradyrhizobium CB756 on sucrose prefermented by yeast

Abstract: LIE, T. A., MUILENBURG, M., HIEP, N. H., and AYHAN, K. 1992. Cultivation of Bradyrhizobiurn CB756 on sucrose prefermented by yeast. Can. J. Microbiol. 38: 569-572. Saccharornyces cerevisiae, grown with sucrose as a substrate, converts the sucrose to glycerol and produces yeast cells. The yield of glycerol was doubled by adding CaCO,. The fermented medium, containing glycerol and yeast cells, was an excellent medium for the cultivation of Bradyrhizobiurn CB756. Best results were obtained after dilution of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A concentration of 10% (w/ v) glucose in the medium, which produced a glycerol yield of 2.58 g/l, was selected for development of glycerol production in further studies, because such a concentration of glucose could be easily achieved through steamed cassava fermentation. We also determined the effect of CaCO 3 on the yield of glycerol from glucose fermentation, since it was known from the literature that addition of CaCO 3 to the medium enhanced glycerol production (Lie et al 1992). The results showed that the addition of 3 g CaCO 3 /l to the medium during yeast fermentation resulted in 67% increase in glycerol production, compared to yeast fermentation without CaCO 3 (Figure 3b).…”
Section: Sources Of Carbon For Different Rhizobiamentioning
confidence: 94%
See 4 more Smart Citations
“…A concentration of 10% (w/ v) glucose in the medium, which produced a glycerol yield of 2.58 g/l, was selected for development of glycerol production in further studies, because such a concentration of glucose could be easily achieved through steamed cassava fermentation. We also determined the effect of CaCO 3 on the yield of glycerol from glucose fermentation, since it was known from the literature that addition of CaCO 3 to the medium enhanced glycerol production (Lie et al 1992). The results showed that the addition of 3 g CaCO 3 /l to the medium during yeast fermentation resulted in 67% increase in glycerol production, compared to yeast fermentation without CaCO 3 (Figure 3b).…”
Section: Sources Of Carbon For Different Rhizobiamentioning
confidence: 94%
“…The yeast culture was maintained as an agar slant in a medium modified from Lie et al (1992). This medium contained 1.0 g urea, 1.0 g KH 2 PO 4 , 0.5 g MgSO 4 AE 7H 2 O, 2.5 g yeast extract and 100 g glucose/l, and its pH was adjusted to 5.0 before autoclaving.…”
Section: Yeast Culturementioning
confidence: 99%
See 3 more Smart Citations